PENYEDERHANAAN AKSES LAYANAN TEKNOLOGI PADA PERANCANGAN USER INTERFACE (UI) WEBSITE PADEK.IN DENGAN METODE DESIGN THINKING: Design Thinking, User Interface, UI Prototype, Usability Testing, User Experience - Kahar, Novhirtamely; Aminuddin, Fattachul Huda; Pratiwi, Eka Melisa (LP2M Universitas Nurdin Hamzah, 2025)
In the era of digital transformation, fast and efficient access to technology services has become a primary need for users. However, interface complexity and a lack of focus on user needs often hinder the use of digital platforms. This study aims to apply the Design Thinking method to the user interface (UI) design of the Padek.In website, with a primary focus on simplifying access to technology services and improving the user experience. This approach is based on diverse user needs, field observations, literature studies, and benchmarking against similar competitors. The research process follows five main stages of Design Thinking: (1) Empathize to explore user needs and obstacles, (2) Define to formulate the core problem, (3) Ideate to generate innovative design solutions, (4) Prototype to create a UI prototype, and (5) Test through usability testing with end users. The result of this process is a prototype UI for the Padek.In website with a simple and intuitive navigation structure, accompanied by complete design documentation and a usability test report.